RESPON TUNARUNGU TERHADAP PENGGUNAAN SISTEM BAHASA ISYARAT INDONESA (SIBI) DAN BAHASA ISYARAT INDONESIA (BISINDO) DALAM KOMUNIKASI - Mursita, Rohmah Ageng (INKLUSI, 2015)
This study aims to examine and find out the information about deaf response towards the use of Indonesian signal language (BISINDO) and Indonesian Signal Language System (SIBI) on communication. Research method being implemented was quantitative approach in which supported by qualitative data. Subject on this study was 100 respondents of adult and teenagers with hearing impairments (aged 1650) who live in Indonesia especially at Java and Bali. Data collection technique on this study was questionnaire and interview. Based on data analysis seen from answer categorization of 100 respondents with hearing impairment, less of them are supporting SIBI on communication because of its concept cause difficulties for communicating. Whereas, most of them supporting the use of BISINDO on communication. Thus, it could be concluded that through the questionnaire result and interview of 100 respondent with hearing impairment on teenagers and adult categorization (aged 1659) in various places, its proven that 91% majority of deaf are using BISINDO for communicate with others.